If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(5x + 4) = 5(x + 1) Reorder the terms: 2(4 + 5x) = 5(x + 1) (4 * 2 + 5x * 2) = 5(x + 1) (8 + 10x) = 5(x + 1) Reorder the terms: 8 + 10x = 5(1 + x) 8 + 10x = (1 * 5 + x * 5) 8 + 10x = (5 + 5x) Solving 8 + 10x = 5 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 8 + 10x + -5x = 5 + 5x + -5x Combine like terms: 10x + -5x = 5x 8 + 5x = 5 + 5x + -5x Combine like terms: 5x + -5x = 0 8 + 5x = 5 + 0 8 + 5x = 5 Add '-8' to each side of the equation. 8 + -8 + 5x = 5 + -8 Combine like terms: 8 + -8 = 0 0 + 5x = 5 + -8 5x = 5 + -8 Combine like terms: 5 + -8 = -3 5x = -3 Divide each side by '5'. x = -0.6 Simplifying x = -0.6
| 9+12x=12x+7 | | 2x*(5x+4)=5*(x+1) | | 20x+14=2x+56 | | y+10=4x+13 | | 11-10x=99-38x | | 8t-7=3t+9 | | 7d(d-3)=0 | | 3(r-2)=5(r+4) | | -2q+3=8q-7 | | 2(3+e)=e+5 | | 48X=12X^3 | | 0=48X-12X^3 | | 3y-3=3x | | 37-a=378 | | -5-(6)= | | 14+8y^2=46 | | 3y-20=2y+8 | | 4x=4y+4 | | 56=20+2x+2y | | (2x-5)-(3x+1)(9-1)=21 | | 6d+5=4d+15 | | -2(x-4)=6(x+2)+3x | | 11-10x=91-24x | | 3x+10y=-6 | | 36x-27x+x= | | 5a+16a-9= | | 2(2c+3m-t)= | | -7x=-2x-(x+8) | | 3(1)-y=6 | | o^2+5o-24=0 | | o^2+50-24=0 | | n^2+3n+2=0 |